The impact of budget deficits, exchange rate regimes and economic sanctions on Iran’s inflation / Hamidreza Ghorbani Dastgerdi - Hamidreza, Ghorbani Dastgerdi (2015)
This study examines the dynamic responses of inflation to its determinants in the short run and long run in Iran from 1970 to 2011. Along with the traditional unit root test of augmented Dickey Fuller (ADF) test, the Zivot and Andrews (ZA) test is performed on all the series to check whether structural break is present in the data. The analysis proceeds with the findings on the relationship between inflation and its determinants in five models of Autoregressive Distributed Lag (ARDL). It incorporates the effect of economic sanctions on inflation in Iran via two approaches. First is by utilizing a dummy variable, while second is by introducing an index, constructed by the principal component model (PCM). To measure inflation persistence and seignorage persistence, the simple interpretive model (SIM) and the grid bootstrap method (GBM) are applied to the data. It clarifies the roles of the fiscal dominance and exchange rate regimes on inflation. Furthermore, the study of inflation persistence examines the gap between monetary policies and the optimal level to control inflation. The findings suggest that budget deficit, the broad money and the exchange rate are main causes of inflation in Iran. Unlike others, oil price shocks and real GDP have negative impact on inflation in Iran. Undoubtedly, economic sanctions augment Iran’s inflation by limiting trade openness and investment inflows. The results uncover the existence of high level of fiscal dominance in Iran’s which driven to higher inflation. Result from inflation persistence shows that monetary policies are working in controlling inflation but they are still far from optimal level. Interestingly, in Iran, the result shows that the fixed exchange iv rate regime is more effective to control inflation rather than the floating exchange rate with inflation targeting. Also, inflation increases with the gap between the official and the market (black) exchange rates.